2007
DOI: 10.1111/j.1474-9726.2007.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in xenobiotic metabolism in the long‐lived Little mice

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 65 publications
7
107
0
Order By: Relevance
“…However, it has also been suggested that induction of genes linked to xenobiotic metabolism plays a significant role in longevity assurance in animals. [59][60][61] Interestingly, the induction of hepatic P450 genes after 18 months of supplementation was largely abrogated, although as we examined only two time-points, we do not know exactly when this actually occurred. However, by 18 months of supplementation, a significant upregulation of several genes associated with the cyclin dependent kinase inhibitor 1A (Cdki1a/p21) signaling pathway was observed, with p38 Mapk up 92%, Mdm2 up 89%, and p21 upregulated 554% (5.5-fold).…”
Section: Discussionmentioning
confidence: 98%
“…However, it has also been suggested that induction of genes linked to xenobiotic metabolism plays a significant role in longevity assurance in animals. [59][60][61] Interestingly, the induction of hepatic P450 genes after 18 months of supplementation was largely abrogated, although as we examined only two time-points, we do not know exactly when this actually occurred. However, by 18 months of supplementation, a significant upregulation of several genes associated with the cyclin dependent kinase inhibitor 1A (Cdki1a/p21) signaling pathway was observed, with p38 Mapk up 92%, Mdm2 up 89%, and p21 upregulated 554% (5.5-fold).…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, we showed that, at least for the three xenobiotics that we tested, the increased xenobiotic resistance and lifespan of IIS mutants are independently mediated traits with no direct, causal connection between them. Increased expression of genes involved in xenobiotic metabolism together with xenobiotic resistance are, nonetheless, common correlates of lifespan extension (7,10,11,(13)(14)(15), raising the question of why this association is so frequent. Interestingly, genes involved in xenobiotic metabolism are indirectly activated by toxic by-products of microbes and pathogens, through the cellular surveillance-activated detoxification and defense (cSADD) system (40), which senses xenobiotics through the dysfunction in cellular processes that they cause, including decreased host translation and altered metabolism (41).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide transcript profiles from long-lived animals, including IIS mutant worms and flies (9, 10), long-lived mutant Ames and Little dwarf mice (11), and mice from crowded litters, subjected to dietary restriction or treated with rapamycin (12) all show increased expression of genes involved in phase 1 and 2 drug and xenobiotic metabolism (13). Little mice are also resistant to toxicity from xenobiotic compounds (14), indicating that the gene expression profiles are physiologically relevant. The link between increased lifespan and xenobiotic metabolism has led to the "Green Theory," which suggests that aging results from an accumulation of xenobiotic and endobiotic toxicity as a consequence of a declining detoxification response with age (15).…”
mentioning
confidence: 99%
“…Amador‐Noguez et al ., 2007). Moreover, in a clinical trial UDCA prevented colorectal adenoma recurrence (Alberts et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%